STRATEGI ADAPTASI ALLIUM TANGERANG HOTEL PADA MASA PANDEMI COVID-19 - Yustisia Kristiana; Daniel Yohanes; Yismaya Irving Gunawan (Universitas Merdeka Malang, 2021)
The COVID-19 pandemic that occurred in March 2020 resulted in a drastic decrease in the occupancy rate of Allium Tangerang Hotel. In April 2020, the room occupancy rate has dropped dramatically. This resulted in the Allium Tangerang Hotel being closed throughout May 2020. Allium Tangerang Hotel is trying to adapt to the COVID-19 pandemic. The research objectives were to (1) describe the impact of the COVID-19 pandemic on Allium Tangerang Hotel, and (2) analyze the adaptation strategy of Allium Tangerang Hotel during the COVID-19 pandemic. The method used is qualitative. The data sources were selected using purposive sampling method. The selected informants were General Manager of Allium Tangerang Hotel, Human Resources Department Manager of Allium Tangerang Hotel, Front Office Manager of Allium Tangerang Hotel, and Front Office Supervisor of Allium Tangerang Hotel. The data analysis technique used in this research is interactive analysis. The findings of the research show that the COVID-19 Allium Tangerang Hotel pandemic must close the hotel operations as a whole which affects labor policies. The strategy used by Allium Tangerang Hotel is downsizing. Allium Tangerang Hotel management has developed a confronting style in supporting adaptation strategies to face the COVID-19 pandemic. The results of this study can encourage the management of Allium Tangerang Hotel for planning in facing crises, especially in the hotel industry for business sustainability.